Rest and exercise haemodynamics in patients with one of two stented bioprostheses and in healthy controls with small aortic annuli. (31st October 2017) - Stock, Sina; Lohmann, Inga; Hanke, Thorsten; Stierle, Ulrich; Richardt, Doreen; Tsvelodub, Stanislav; Sievers, Hans-Hinrich
Abstract: OBJECTIVES: Because bioprosthetic aortic valve replacement remains one of the most frequent cardiac surgical procedures, it is necessary to study patient haemodynamics in more detail. Until now, a few studies assessed haemodynamics during exercise, but none with special regard to small aortic annuli. We compared patients who had the differently designed bioprostheses, Trifecta and Perimount Magna Ease (PME), size ≤ 23 mm, and a healthy control group during rest and exercise. METHODS: We determined the mean transvalvular gradient, the effective orifice area (EOA) and the EOA index during rest and exercise using transthoracic echocardiography in 35 patients with the Trifecta (mean age 71.4 years, follow-up 1 year, labelled valve size 21.7 mm), in 16 patients with the PME (mean age 66.2 years, follow-up 2.6 years, labelled valve size 21.6 mm) and in 25 healthy persons. The parameters derived were summarized in a simplified Valve Academic Research Consortium-2 classification to determine prosthetic valve dysfunction. RESULTS: When we compared the Trifecta and the PME, a significant superiority of the Trifecta was seen at rest in mean transvalvular gradient (7.96 vs 12.19 mmHg) and EOA (1.57 vs 1.48 cm 2 ), during exercise in all parameters (mean transvalvular gradient 11.06 vs 19.2 mmHg, EOA 1.77 vs 1.26 cm 2, EOA index 0.96 vs 0.67 cm 2 /m 2 ). The Trifecta showed a physiological increase in the EOA index during exercise. Exercise led to a shift to better simplified Valve Academic Research Consortium-2 categories in the Trifecta and to worse in the PME group. CONCLUSIONS: This study reveals the haemodynamic superiority of the Trifecta to the PME. Especially in small aortic annuli, this difference might have some relevance for clinical and research issues.